Single-Phase Silicate Phosphors (Ba1.3Ca0.7−xSiO4:xDy3+) Doped with Dysprosium for White Solid-State Lighting. (24th May 2022) - Golja, Desta R.; Dejene, Francis B.; Kim, Jung Yong
Abstract : Single-phase phosphors have potential advantages such as simple processability, competitive cost, and other optical and optoelectronic properties. Hence, in this study, the silicate phosphors (Ba1.3 Ca0.7− x SiO4 : x Dy 3+ ) doped with Dy 3+ ions ( x = 0.01–0.05) were synthesized and characterized in detail. X-ray diffraction patterns showed that all the silicate phosphors have a τ -phase hexagonal unit cell independent of doping. However, d -spacing was reduced for the doped samples, indicating that the interplanar interactions were enhanced. Resultantly, the doped phosphors exhibited relatively larger domains with connectivity than the host, although there were sometimes microscale pores. Photoluminescence spectra stipulated that the optimized doping concentration is x = 0.03 for the silicate Ba1.3 Ca0.7- x SiO4 : x Dy 3+ phosphors. Finally, the CIE coordinates (0.30, 0.33) confirm that the Dy 3+ -doped silicate phosphors are well applicable to the white light-emitting diodes for solid-state lighting and display devices.